Die Auswirkungen der Kritik der reinen Vernunft von I. Kant auf die Sprachphilosophie - Andrzejewski, Bolesław (Studia Germanica Posnaniensia, 2018)
The aim of this article is to show the influence of I. Kant's methodology on the development of modern philosophy of language. The author discusses the selected standpoints inspired in this respect by the Kantian "Copernican revolution" and apriorism. The starting point of considerations are W. v. Humboldt's views for whom language is a spontaneous "emanation of spirit", the result of incessantly active internal powers of man. Humboldtism influenced a number of later conceptions. One of them is "generative grammar" of N. Chomsky's American school, although there are also present in this case influences of nativistic interpretations. In a more distinct manner the Kantian-Humboldtian apriorism has influenced the "symbolic" philosophy of E. Cassirer and the linguistic "relativism" of E. Sapir, B. L. Whorf and L. Weisgerber. Their views are presented in the next part of the work. The article ends with the discussion of H. Glinz's philosophical and linguistic views which are based in great measure also on the Kantian methodology.